Novos compósitos cerâmicos com base em caulim, borra de tinta, areia de fundição e vidros residuais - Ribas, Hélverton Emílio (2017)
Industrial waste has been one of the major environmental problems discussed today. Many contain in their compositions heavy metals of various contents, and an analysis of each residue is necessary in order to find appropriate practical solutions of the destination, and become a benefit to the environment. Several compositions were made with paint sludge, cast sand, glass and kaolin, in 60mmx20mm molds, uniaxially pressed in a hydraulic press at 10 MPa and sintered in an electric oven at temperatures of 1100 ° C, 1150 ° C ° C, 1200 ° C, 1250 ° C and 1275 ° C. The composites underwent tests of resistance to bending, water absorption, apparent density, linear retraction, FRX, DRX, SEM, EDS, leaching and analysis of particulate materials. Subsequently, in the sintered material, new physical and mechanical properties were found, showing the casting of its materials and flexural strength of 12.29 Mpa, 10.85% of water absorption. 6.04% linear retraction and 1.39% apparent densities, in the composition that was used of 7% of residues and incinerated at 1275 ° C. It identified the presence of the minerals montmorillonite, illite, kaolinite, gibbsite, rutila and cristobalite and their influences on ceramics. This research presented a suitable solution for waste ink, sand casting and glass, using them as raw material for white ceramics.